Tingkat Kepuasan Konsumen terhadap Tanaman Hias di Bursa dan Pelelangan Menggung Forest Art 2 Kecamatan Tawangmangu - Sari, Erlina Novita; Santosa, Muhammad Elsa; Anggara, Muhammad Fariskan; Prasetyo, Agung (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2022)
Consumers have an important role in the business world, one of which is the ornamental plant business. Consumer satisfaction was strongly influenced by the level of income, where consumers have a decision in choosing a product they will buy. Knowledge of consumer perceptions is important to increase farmers' income. This research method uses a descriptive approach, where data collection was carried out using interviews and direct surveys. Data were analysed using the Consumer Satisfaction Index (CSI). The level of consumer satisfaction with ornamental plants on the stock exchange and the auction of ornamental plants at Menggung Forest Art 2 was classified into the very satisfied category. Consumer satisfaction with ornamental plants is influenced by attributes such as variety, level of product uniqueness, product prices, future price predictions, and the appearance of plants in pots. Improvements regarding the selection of pots that are more adapted to the size of the plant and the selection of pot colours need to be made by traders or ornamental plant auctioneers.